2021
DOI: 10.3390/ma14164417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Chloride Resistance of Polypropylene Fiber Reinforced Concrete with Fly Ash and Modeling

Abstract: Herein, the paper reports an experimental investigation lasting one year on the chloride resistance of polypropylene fiber (PF) reinforced concrete with fly ash (FA). Four influential factors at four levels were studied, viz. water to binder ratio (w/b) (0.53, 0.34, 0.29, and 0.25), PF dosage (0%, 0.06%, 0.08%, and 0.1% in volume basis of the total volume of concrete), FA content (0%, 15%, 25%, and 35% in mass substitution ratio of cement) and concentration of NaCl solution (0%, 3%, 5%, and 7%). Dry–wet cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, further increase of the waste nylon fiber reduces the chloride ion penetration resistance in the concrete matrix compared to the control mixture. The same observation with Chen et al [ 117 ] found that increasing the replacement of synthetic fiber can downfall concrete chloride migration resistance. This is mainly due to the reason the higher replacement of waste synthetic fiber can cause the void occurrence in the concrete matrix that can allow the migration of chloride.…”
Section: Effect Of Wsf On Durabilitysupporting
confidence: 74%
See 1 more Smart Citation
“…However, further increase of the waste nylon fiber reduces the chloride ion penetration resistance in the concrete matrix compared to the control mixture. The same observation with Chen et al [ 117 ] found that increasing the replacement of synthetic fiber can downfall concrete chloride migration resistance. This is mainly due to the reason the higher replacement of waste synthetic fiber can cause the void occurrence in the concrete matrix that can allow the migration of chloride.…”
Section: Effect Of Wsf On Durabilitysupporting
confidence: 74%
“…Especially, the study found employing waste synthetic fibers by 1 % to the weight of concrete is 10 % more resistant than conventional concrete. This is mainly due to waste synthetic fibers are impermeable materials and can permit good holding together of the concrete matrix that mitigates the entrance of chloride ions and resists the corrosion of steel bars in concrete structures [ 117 , 119 , 120 ].…”
Section: Effect Of Wsf On Durabilitymentioning
confidence: 99%
“…Incorporating supplementary cementitious materials (SCMs) in concrete to assess their influence on fresh and hardened properties and durability of concrete has been discussed and widely promoted [8][9][10][11][12][13][14][15][16][17]. The researchers have acknowledged using F-FA to enhance concrete's fresh and hardened properties [4,5,9,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete mixes containing varying amounts of F-FA with the highest replacement volume (35%) and PP fibers between 0-0.1%, investigated for chloride resistance, show reduced chloride ingress for a water-binder ratio of 0.25. Resistance to chloride increases with a higher fiber content and F-FA volume [16]. Studies on using hybrid fibers such as PP, coated basalt fibers, steel fibers, and their influence on engineered cement composites containing high-volume F-FA show that hybridization helps improve such composites' strength and durability [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from traditional pozzolanic materials such as fly ash and furnace slag, many researchers have tried to find new materials that are more adaptable to the local situation. For example, it was reported that marine clay can be utilized with high added value as a supplementary binding material in manufacturing sustainable concrete products [22,23]. Recycled fine aggregates and recycled glass powder can be co-used in concrete production, which reduces the total carbon dioxide emission by about 19% [24,25].…”
Section: Introductionmentioning
confidence: 99%